SCIENTIFIC PEDAGOGICAL FUNDAMENTALS OF THE USE OF GAME TECHNOLOGY IN PEDAGOGICAL LESSONS - M.Zoirova (Journals Park Publishing, 2022)
This article provides information that the game is one of the main activities along with work and study, according to the research of scientists.
Keywords: pedagogy; lesson; game